2020
DOI: 10.7717/peerj.8683
|View full text |Cite
|
Sign up to set email alerts
|

Patterns of change in α and β taxonomic and phylogenetic diversity in the secondary succession of semi-natural grasslands in the Northern Apennines

Abstract: We studied the secondary succession in semi-natural grasslands (dry grasslands and hay meadows) located in the eastern side of the Tuscan Apennines (Tuscany, Central Italy). We compared these habitats, investigating: (i) the changes in species richness, composition and phylogenetic diversity during the succession; (ii) whether the trends in species loss and species turnover in taxonomic diversity matched those in phylogenetic diversity. We performed a stratified random sampling, in a full factorial design betw… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 51 publications
0
6
0
Order By: Relevance
“…As succession progresses, the different facets of diversity undergo differential patterns of change (Lohbeck et al, 2012;Vellend et al, 2013;Yuan et al, 2016). Both increasing and decreasing trends of taxonomic diversity during grassland succession have been reported (Purschke et al, 2013;Lazzaro et al, 2020). The phylogenetic alpha diversity significantly increased from the early-mid to late-successional stages but with no significant changes detected in the early and early-mid successional stages in an arable-to-grassland chronosequence more than 270-years-long (Purschke et al, 2013).…”
Section: Introductionmentioning
confidence: 98%
“…As succession progresses, the different facets of diversity undergo differential patterns of change (Lohbeck et al, 2012;Vellend et al, 2013;Yuan et al, 2016). Both increasing and decreasing trends of taxonomic diversity during grassland succession have been reported (Purschke et al, 2013;Lazzaro et al, 2020). The phylogenetic alpha diversity significantly increased from the early-mid to late-successional stages but with no significant changes detected in the early and early-mid successional stages in an arable-to-grassland chronosequence more than 270-years-long (Purschke et al, 2013).…”
Section: Introductionmentioning
confidence: 98%
“…Pelato are the only ones hosting a fern (Asplenium ceterach L.). It has already been shown that the presence of a single species characterized by a deep separation in the phylogeny of the communities may raise substantial differences in phylogenetic trends (Lazzaro et al 2020).…”
Section: Discussionmentioning
confidence: 99%
“…The main idea behind this approach is to interpret taxa phylogenetic positions as result of evolutionary processes, such as extinction (Purvis et al, 2000), speciation (Winter et al, 2009) and biological invasion (Srivastava et al, 2012). It has already become widely accepted that merging the phylogenetic and functional information allows to better quantify the impact of disturbances and to understand the processes contributing on plant community dynamics (Flynn et al, 2011;Perronne et al, 2014;Dehling et al, 2014;Hao et al, 2018;Chun and Lee, 2019;Lazzaro et al, 2020b).…”
Section: Introductionmentioning
confidence: 99%